2021
DOI: 10.1080/19585969.2022.2042163
|View full text |Cite
|
Sign up to set email alerts
|

Chemical sex (chemsex) in a population of French university students

Abstract: Introduction Chemsex is defined by the use of psychoactive substances to facilitate or improve sexual relations. Our objectives were to assess the prevalence of the practice of ‘chemsex’ in a population of French university students and to identify socio-demographic and clinical factors associated with this practice. Material and methods We have used an anonymous online questionnaire comprising 15 questions on socio-demographic characteristics, chemsex use, sexual satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Nonetheless, there are limited data available on the prevalence of females in chemsex. One study by Malandain et al [23] also found no significant differences in the prevalence of chemsex between males and females. This evidence, combined with our findings, should serve as a starting point for a more in-depth investigation into the relationship between gender and chemsex.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nonetheless, there are limited data available on the prevalence of females in chemsex. One study by Malandain et al [23] also found no significant differences in the prevalence of chemsex between males and females. This evidence, combined with our findings, should serve as a starting point for a more in-depth investigation into the relationship between gender and chemsex.…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, out of the 1,828 individuals who responded to the survey, 1,124 were females, accounting for 7.92% of the entire sample, while male chemsex users constituted 8.64% of the total sample. It is worth noting that women are often more likely than men to participate in online surveys [22, 23] and our results may reflect this bias. Nonetheless, there are limited data available on the prevalence of females in chemsex.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that improvement of sexual abilities was also described as a reason to consume cocaine, amphetamine or methamphetamine raises the issue of chemsex, i.e., the use of psychoactive substance to initiate, facilitate, improve and prolong sexual experiences, which has been described as highly prevalent in students in a recent study (Malandain et al. 2021 ). Improving sexual performance was also a reported reason for using NPS, heroin and LSD, with injectable routes used for NPS and heroin, suggesting slamming practices.…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of these substances was not frequently reported, chemsex practices expose students to complications such as substance use disorders, acute neurological or cardiovascular intoxications, various psychiatric disorders, and viral and bacterial infections (Malandain et al. 2021 ; Batisse et al. 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The reported prevalence of over 20% of chemical sex in university students (Malandain et al. 2021 ) is concerning and suggest that more research and knowledge dissemination about this topic to clinicians is urgently needed. Crocq ( 2021 ) describes the evolution of the concept of gender dysphoria from Ancient Greek and Roman times to the current DSM.5 and ICD-11, providing critically important insights for clinicians.…”
mentioning
confidence: 99%